Chemical, morphological and structural characteristics of crossbred wool fibers. Issue 5 (3rd May 2020) - Ghermezgoli, Zahra Mohammadi; Moghaddam, Meghdad Kamali; Moezzi, Meysam
Abstract: Crossbreeding of a local sheep called Ghezel thick wool with Arkharmerino fine wool is one of the interest studies in the last decade to improve the local sheep's products quality. In this study, the chemical and mechanical properties of Arkharmerino, Ghezel and their first and second-generation wool fibers were investigated. The diameter, length and tensile properties of wool fibers were studied. The Fourier transform infrared spectroscopy, scanning electron microscope, X-ray diffraction and energy dispersive X-ray spectrum were also performed to evaluate the morphological and physical characteristics of all samples. The results showed that crossbreeding Ghezel ewes with Arkharmerino rams led to improving the wool fiber characteristics from chemical and physical properties points of view in the final application. The higher fineness, higher length, lighter color and higher tenacity were resulting from Arkharmerino–Ghezel in the second generation in comparison with Ghezel wool fibers.